GROWTH AND INFRASTRUCTURE INVESTMENT IN INDIA: ACHIEVEMENTS, CHALLENGES, AND OPPORTUNITIES - Kumar Mishra, Aswini; Narendra, Kunapareddy; Prasad Kar, Bibhu (Economic Annals, 2013)
The paper analyses the recent scenario of infrastructure investment in India, with the recognition that inadequate infrastructure is one of the major constraints on India’s ability to sustain high GDP growth. It conducts an overview of the trends in infrastructure investment from the 10th Five Year Plan onwards, and tries to examine the linkage between infrastructure and economic growth. The results exhibit a very high rate of return and also highlight that, since resource constraints will continue to limit public investment in infrastructure in other areas, Public Private Partnership (PPP) project-based development needs to be encouraged wherever feasible.